Vitiligo after alemtuzumab treatment: Secondary autoimmunity is not all about B cells. (11th December 2018) - Ruck, Tobias; Pfeuffer, Steffen; Schulte-Mecklenbeck, Andreas; Gross, Catharina C.; Lindner, Maren; Metze, Dieter; Ehrchen, Jan; Sondermann, Wiebke; Pul, Refik; Kleinschnitz, Christoph; Wiendl, Heinz; Meuth, Sven G.; et al.
Abstract : Objective: To report 3 patients with relapsing-remitting multiple sclerosis (RRMS) showing vitiligo after treatment with alemtuzumab. Methods: Retrospective case series including flow cytometric analyses and T-cell receptor (TCR) sequencing of peripheral blood mononuclear cells. Results: We describe 3 cases of alemtuzumab-treated patients with RRMS developing vitiligo 52, 18, and 14 months after alemtuzumab initiation. Histopathology shows loss of epidermal pigmentation with absence of melanocytes and interface dermatitis with CD8 + T-cell infiltration. Also compatible with pathophysiologic concepts of vitiligo, peripheral blood mononuclear cells of one patient showed high proportions of CD8 + T cells with an activated (human leukocyte antigen–DR + ), memory (CD45RO + ), and type 1 cytokine (interferon-γ + tumor necrosis factor–α) phenotype at vitiligo onset compared to a control cohort of alemtuzumab-treated patients with RRMS (n = 30). Of note, analysis of CD8 TCR repertoire in this patient revealed a highly increased clonality and reduced repertoire diversity compared to healthy controls and treatment-naive patients with RRMS. We observed a predominance of single clones at baseline in this patient and alemtuzumab treatment did not substantially affect the proportions of most abundant clones over time. Conclusion: The 3 cases represent a detailed description of vitiligo as a T-cell-mediated secondary autoimmune disease following alemtuzumab treatment. The prevailing concept of unleashed B-cell responses might therefore not cover all facets of alemtuzumab-related secondary autoimmunity. Mechanistic studies, especially on TCR repertoire, might help clarify the underlying mechanisms.